Forgoing health care is associated with insurance deductibles in a consumer-driven health care system. (30th September 2020) - Sandoval, J L; Petrovic, D; Guessous, I; Stringhini, S
Abstract: Background: The Swiss health care system is consumer-driven with universal coverage and good population outcomes. Deductibles of mandatory insurance plans are self-selected, regulated, and unrelated to pre-existing conditions. In a Swiss population, we aimed to determine if forgoing health care was associated with insurance plan deductibles and if the association was dependent on socioeconomic status. Methods: We used data from the Bus Santé Study; a cross-sectional survey study ongoing in Geneva (Switzerland) since 1993. We included adult participants in the study between 2007 and 2016. We divided participants according to insurance plan deductibles (low, medium, or high). Forgoing health care information was obtained from the study questionnaire. Forgoing dental health care was considered separately as mandatory insurance plans do not cover dental care. Inequalities were quantified using the regression-based relative index of inequality (RII) adjusted for potential confounders (age, gender, income, educational attainment, known comorbidities, cardiovascular risk factors, additional health insurance plans or subsidized premiums) Results: We included 9081 participants, with 8.9% reporting forgoing non-dental healthcare. Those with a high-deductible insurance plan were younger, more often Swiss and male, with higher income and educational attainment, less known cardiovascular risk factors and comorbidities. Participants with high-deductible plans had a higher probability of forgoing non-dental health care (RII=2.2, p < 0.001) independently of socioeconomic status and known comorbidities or cardiovascular risk factors. As expected, we did not observe inequalities related to insurance plan deductibles in forgoing dental health care (RII=1.0, p = 0.8). Conclusions: In a population with universal coverage and good health outcomes, insurance plan deductibles are associated with inequities in forgoing health care independently of socioeconomic status and pre-existing conditions. Key messages: In a highly performant health system, high insurance plan deductibles are associated with inequities in care independent of individual sociodemographic characteristics, risk factors and comorbidities. Uncovering associations between health system design features and inequities in care could inform decision-makers that seek to curtail inequities through improving their current health system design.